Effects of natural plant growth regulator iron chlorin on photosynthesis, yield, and quality of watermelons grown in greenhouses - Qian Feng; Lu Lu; Qingyun Li; Liu Wang; Qingyu Pei; Shoujiang Pan; Jing Tian; Shaowei Lu; Shao Li (Horticultural Science)
Iron chlorin is known to affect plant growth, but its potential applications in watermelon production have rarely been explored. To better understand its effects on the growth, photosynthesis, yield, and quality of watermelon in a greenhouse setting, a series of experiments were conducted using the variety 'Sumeng 6'. At the flowering and early fruit expansion stages, the plants were sprayed with iron chlorin with mass concentrations of 0.001, 0.002, 0.004, and 0.008 μg/L (T1, T2, T3, and T4). Control plants were sprayed with water (CK). The growth index, root activity, photosynthetic pigment content, photosynthetic parameters, yield, and fruit quality of all plants were measured. The results showed: compared with CK, the T3-treated plants showed significant improvements in several aspects: the leaf contents of photosynthetic pigments, chlorophyll a, total chlorophyll, and carotenoid, increased by 19.51%, 14.29%, and 29.17%, respectively (P < 0.05); the net photosynthetic rate (Pn) increased by 23.60% (P < 0.05); and the soluble solids content, vitamin C content, and yield increased by 7.89%, 34.13%, and 16.27%, respectively (P < 0.05). In summary, it was found that spraying 0.004 μg/L iron chlorin on facility watermelon plants at the flowering and the early fruit expansion stages has a significant effect on the promotion of growth and development, leading to improved quality and yield. This study provides a theoretical reference and technical guide for high-quality and efficient watermelon production.